Faktor Pendorong Pendirian Bangunan di Sempadan Rel Kereta Api Stasiun Tanjung Karang - Syifa Novia Tabrani; Rahayu Sulistyorini; Ahmad Herison (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. Spatial planning in urban transportation areas faces increasing pressure due to population growth and limited land, which encourages the emergence of buildings in areas that should be protected, such as railway borders. This condition has the potential to cause safety risks and irregularities in urban spatial planning. This study aims to analyze factors related to the reasons for people to build buildings in the railway border area, especially around Tanjung Karang Station, Bandar Lampung City. The method used is a field survey with a quantitative approach and Spearman Rank correlation analysis processed using the SPSS 24 program. Respondents consisted of 96 people spread across five villages in two districts. The results of the study indicate that factors suspected of being related to the reasons for people to build buildings consist of the role of the provincial government, the role of the city government, education level, knowledge level, length of residence, social networks, environmental quality, the presence of trade and service centers, economic factors, and land ownership status. Based on the results of the hypothesis test, the factors that are strongly related are the role of the provincial government, knowledge level, social networks, environmental quality, the presence of trade and service centers, and economic factors. Abstrak. Penataan ruang kawasan transportasi perkotaan menghadapi tekanan yang semakin besar akibat pertumbuhan penduduk dan keterbatasan lahan, yang mendorong munculnya bangunan pada kawasan yang seharusnya dilindungi seperti sempadan rel kereta api. Kondisi ini berpotensi menimbulkan risiko keselamatan serta ketidakteraturan tata ruang perkotaan. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang berhubungan dengan alasan masyarakat mendirikan bangunan di kawasan sempadan rel kereta api, khususnya di sekitar Stasiun Tanjung Karang, Kota Bandar Lampung. Metode yang digunakan adalah survei lapangan dengan pendekatan kuantitatif dan analisis korelasi Rank Spearman yang diolah menggunakan program SPSS 24. Responden terdiri dari 96 orang yang tersebar di lima kelurahan di dua kecamatan. Hasil penelitian menunjukkan bahwa faktor-faktor yang diduga berhubungan dengan alasan masyarakat untuk mendirikan bangunan terdiri dari peran pemerintah provinsi, peran pemerintah kota, tingkat pendidikan, tingkat pengetahuan, lama tinggal, jaringan sosial, kualitas lingkungan, keberadaan pusat perdagangan jasa, ekonomi, dan status kepemilikan lahan. Berdasarkan hasil uji hipotesis, faktor-faktor yang berhubungan kuat yaitu peran pemerintah provinsi, tingkat pengetahuan, jaringan sosial, kualitas lingkungan, keberadaan pusat perdagangan dan jasa dan faktor ekonomi.